Orthographic competencies and phonological awareness in children with developmental coordination disorder - Janjić, Jovana; Nikolić, Snežana; Ilić Stošović, Danijela (Specijalna edukacija i rehabilitacija, 2021)
Introduction. Developmental coordination disorder is a disorder of planning and coordination of complex movements during action, without previously diagnosed intellectual disability, neurological or any other sensory impairment. Although it is a relatively common disorder in school-age population, the correlation between phonological awareness and spelling in these children has not been sufficiently investigated. Objective. The aim of this study was to determine the relationship between phonological awareness and spelling in children with developmental coordination disorder compared to children without coordination difficulty. Methods. The research included 65 children of the third grade of primary schools in Belgrade. Developmental coordination disorder was observed in 29 children, while 36 children did not have this disorder. The Questionnaire for Developmental Coordination Disorder was used to determine its presence. Phonological awareness was assessed by the Test of Phonological Awareness, and spelling by dictation. Results. The results show significant below-average achievements in the assessment of phonological awareness and spelling in children with developmental coordination disorder. Phonemic substitution was the least developed element of phonological awareness. The largest number of errors was observed at the word level, while substitution was the most common error at the syllabic and letter level. A positive correlation between phonemic segments and achievements in spelling indicates a relationship between the sublexical level and spelling development. Conclusion. Poor phonological awareness and spelling ability lead to learning disabilities during the educational process, which results in an overall poorer educational achievement in these children.
Keywords: developmental coordination disorder; phonological awareness; spelling; Serbian language